CBX7 is Dualistic in Cancer Progression Based on its Function and Molecular Interactions - Li, Jun; Ouyang, Taohui; Li, Meihua; Hong, Tao; Alriashy, MHS; Meng, Wei; Zhang, Na (Frontiers in Genetics, 2021)
Chromobox protein homolog 7 (CBX7) is a member of the Chromobox protein family and participates in the formation of the polycomb repressive complex 1(PRC1). In cells, CBX7 often acts as an epigenetic regulator to regulate gene expression. However, pathologically, abnormal expression of CBX7 can lead to an imbalance of gene expression, which is closely related to the occurrence and progression of cancers. In cancers, CBX7 plays a dual role; On the one hand, it contributes to cancer progression in some cancers by inhibiting oncosuppressor genes. On the other hand, it suppresses cancer progression by interacting with different molecules to regulate the synthesis of cell cycle-related proteins. In addition, CBX7 protein may interact with different RNAs (microRNAs, long noncoding RNAs, circular RNAs) in different cancer environments to participate in a variety of pathways, affecting the development of cancers. Moreover, CBX7 is involved in cancer-related immune response and DNA repair. In conclusion, CBX7 expression is a key factor in the occurrence and progression of cancers.